2017
DOI: 10.1017/jmo.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

The role of temporal flexibility on person–environment fit and job satisfaction

Abstract: The present study investigated the role of temporal flexibility on three conceptualizations of person–environment fit and job satisfaction. Data were collected from 320 full-time employees in Canada and America. Using structural equation modeling, it was found that temporal flexibility was directly related to increased job satisfaction and indirectly related to job satisfaction through supplementary fit, demands–abilities fit, and needs–supplies fit. Moreover, supplementary fit and demands–abilities fit were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Individuals who have a strong autonomy orientation are likely to perceive autonomy-supporting contexts, such as BWAs, as providing control rather than as controlling (Vansteenkiste et al, 2010). We posit that a strong autonomy orientation makes individuals prone to identify/recognize BWAs as an opportunity to experience a sense of choice and to show self-determined behaviour (Gerdenitsch et al, 2015;Irak & Mantler, 2018). Autonomy-oriented individuals' inclination to choose contexts that offer autonomy, such as jobs that allow initiative and making choices (Gagné et al, 2018), supports this assumption.…”
Section: Autonomy Orientation As a Moderatormentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who have a strong autonomy orientation are likely to perceive autonomy-supporting contexts, such as BWAs, as providing control rather than as controlling (Vansteenkiste et al, 2010). We posit that a strong autonomy orientation makes individuals prone to identify/recognize BWAs as an opportunity to experience a sense of choice and to show self-determined behaviour (Gerdenitsch et al, 2015;Irak & Mantler, 2018). Autonomy-oriented individuals' inclination to choose contexts that offer autonomy, such as jobs that allow initiative and making choices (Gagné et al, 2018), supports this assumption.…”
Section: Autonomy Orientation As a Moderatormentioning
confidence: 99%
“…Individuals also strive for autonomy because experiencing a sense of autonomy is an inherent human need (Deci & Ryan, 2000) whose satisfaction is positively linked to experiencing positive affective-motivational states (e.g., Wörtler et al, 2020). BWAs could be perceived as an opportunity to fulfil this need (Deci et al, 2017;Gerdenitsch et al, 2015;Irak & Mantler, 2018). Furthermore, freedom to decide when and where to work allows employees to more flexibly take care of non-work-related responsibilities (e.g., personal appointments) and meeting demands such as caring for children and elderly relatives (R. J.…”
Section: Organizational Attractiveness and Ocb Intentions As Outcomesmentioning
confidence: 99%
“…For work abilities, one study of GPs in Shanghai found that GPs perceived managerial competence, creativity and entrepreneurship important for their careers [ 62 ]. These features should then be considered into the design of job opportunities for GPs to meet their demands-abilities fit [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This interesting division of factors predicting differences in attitudes at the end of conscription training can be effectively interpreted from an interactional perspective, or so-called Person-Environment framework where the match or fit between the person and environment (Doruk & Janet, 2018) or group (Li et al, 2018) or task (Wronska et al, 2018) is emphasized in relation to different outcomes. Relationships between individual personality profiles and situational perception (Parmak et al, 2013) as well as psychological well-being in a military task-environment (Parmak et al, 2014) are also established in military settings.…”
Section: Discussionmentioning
confidence: 99%